João Franco: a liberal education (1855-1897) - Ramos, Rui (2001)
João Franco 's success is also due to the fact that many historians saw his government of 1906-1908 as an example of the anti-liberal tendencies that would characterise Salazarism. This study on the beginnings of Franco's political career, from his election as member of parliament in 1884 to the government of 1893-97, considers this approximation between Franco and Salazar as spurious and suggests that the most adequate context in which to comprehend João Franco is the reformist tradition of the liberal elite of the 19th century and not the anti-liberalism of the century.